The Level of Efficiency, Elasticity and Marketing Distribution Pattern of Mango (Mangifera Indica L.) on Critical Land in Plandaan District, Jombang Regency - Alawi Muhammad; Zulfikar Zulfikar (AGARICUS: Advances Agriculture Science & Farming, 2021)
This study aims to analyze marketing distribution patterns, analyze the efficiency and elasticity of distribution of mangoes cultivated on critical land. The data collection method was purposive random sampling and descriptive qualitative and quantitative data analysis. The results showed that there were two levels of mango marketing channels from farmers to consumers, namely local and national marketing channels. The local level marketing channels include three institutions, namely producers, retailers, and consumers, while the national level marketing channels include four institutions, namely: producers, wholesalers, retailers, and consumers. The efficiency value (EP) of the two marketing channels is 0.5%, which means that both marketing channels are efficient marketing channels. The value of transmission elasticity (ET) for local distribution is 0.61 and 0.17 for national distribution, which is generally less than 1. This indicates that the rate of price change at the consumer level is greater than the rate of change in prices at the farm level.